Laju Pertumbuhan Karang Transplantasi Acropora sp. di Pantai Pandawa, Bali - Utami, Mayang; Arthana, I Wayan; Ernawati, Ni Made (Current Trends in Aquatic Science; Vol 4 No 2 (2021), 2022)
Coral transplantation is a coral rehabilitation activity by cutting coral from a colony to be replanted. This study aimed to determine the differences in the growth of coral transplants of Acropora sp. using cement media and pipe media. Research on coral transplantation was carried out at the end of December 2020 to early March 2021 for 3 months at Pandawa Beach, Bali. Observations of coral growth using different media were carried out 6 times with an interval of 14 days using a caliper. Observations on the growth of coral fragments consisted of increasing the height and width of the coral. The results showed that the coral height of Acropora sp. using pipe media has the highest growth rate of 39.34 mm, coral height growth using cement media is 30.31 mm. The result of the highest growth width on coral using pipe media is 30.90 mm and the growth of coral width on cement media is 28.76 mm. The survival rate of coral Acropora sp. on cement media by 100% and on pipe media by 90%.